2010
DOI: 10.1364/boe.1.000126
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection limits using a hand-held optical imager with coregistration capabilities

Abstract: Optical imaging is emerging as a non-invasive and non-ionizing method for breast cancer diagnosis. A hand-held optical imager has been developed with coregistration facilities towards flexible imaging of different tissue volumes and curvatures in near real-time. Herein, fluorescence-enhanced optical imaging experiments are performed to demonstrate deeper target detection under perfect and imperfect (100:1) uptake conditions in (liquid) tissue phantoms and in vitro. Upon summation of multiple scans (fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Optical designs 22 as well as improvements in the instruments and the techniques have been approached. 23 26 …”
Section: Introductionmentioning
confidence: 99%
“…Optical designs 22 as well as improvements in the instruments and the techniques have been approached. 23 26 …”
Section: Introductionmentioning
confidence: 99%
“…The positional tracking capability allowed registration of the optical images with respect to the imaged tissue geometry, and hence provided 3D volumetric analysis as well (34). Extensive tissue phantom studies were performed to demonstrate 3D tomographic imaging capabilities of the imager (30, 35) as well as improved target depth detection (36). In vivo 3D tomographic breast imaging studies (on healthy subjects containing superficially placed tumor-like targets) were demonstrated using the hand-held optical imager (33).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested diffuse optical tomography for hematoma detection; however, this approach is costly, requires large instrumentation, and is not as available as a handheld, real-time solution on the full adult head. Another recent approach uses 3D localization to register multiple images collected with a handheld device [ 20 ]; this is a similar idea to that presented here, but is still effectively concerned with using static imaging. Other, so called moving, devices do exist (such as [ 21 ]), but they are also designed to make static measurements at discrete locations, as opposed to taking measurements as the device itself tracks.…”
Section: Introductionmentioning
confidence: 99%